Волонтерська діяльність закарпатських студентів під час російсько-української війни 2022 року - Поллоі Каталін; Pallay Katalin; Фейнєш Гайналка; Fényes Hajnalka; Маркош Валерія; Markos Valéria (Видавничий центр КНЛУ, 2023)
Резюме. Під час російсько-української війни 2022 року велику роль відіграла та закарпатська молодь, яка в якості волонтерів допомагала біженцям на Закарпатті, на українсько-угорському кордоні та в Угорщині. У пошуковому дослідженні проведені напівструктуровані інтерв’ю із закарпатськими молодими волонтерами. У тематичному аналізі простежено, який волонтерський досвід мали респонденти до війни, що притаманне для їхньої волонтерської діяльності під час війни, що мотивувало їх долучитися до волонтерства і, зрештою, яку користь це може їм принести. На підставі результатів інтерв’ю ми здійснили аналіз типів волонтерів, виділивши три основні типи на основі мотивацій та регулярності здійснення волонтерської діяльності. Найголовнішим результатом нашого дослідження стало те, що попри зростання суспільної напруженості через війну для закарпатських студентів-волонтерів притаманне сильне почуття солідарності з українцями, які приїхали до області з інших регіонів. Крім цього, за час волонтерської діяльності зросло їхнє почуття well-being (духовного благополуччя). Також було з’ясовано, що та частина респондентів, яка почала волонтерити тільки під час війни, ймовірно продовжить таку діяльність і в майбутньому. Завдяки цьому культура волонтерства пошириться в аналізованому регіоні ще більше.

Abstract. Introduction. Under the influence of increased individual and social responsibility, as well as global and local challenges, volunteering as a responsible social role and a form of active social activity began to develop rapidly in Ukraine. During the Russian-Ukrainian war of 2022, Transcarpathian youth played a major role as volunteers, helping refugees in Transcarpathia, on the Ukrainian- Hungarian border, and in Hungary. Purpose. The authors of the article have investigated the young volunteers’ experience before the war, the characteristics of their volunteer activities during the war, and their motivation for the volunteer activity in order to find out the possible positive outcome of their activities. Methods. In the research, the authors have carried out the theme analysis by conducting semi-structured interviews with young volunteers from Transcarpathia. In addition to the theme analysis along the interviews, they also prepared a type-analysis and differentiated between three volunteer-types (regular volunteers with altruistic motivations, regular volunteers with mixed motivations, and occasional volunteers with mixed motivations). Results. The most important result of the research is that young volunteers from Transcarpathia are characterized by strong solidarity for the Ukrainian refugees despite the social tension arising as a result of the war. Another important finding may be that the group of respondents who only started to volunteer during the war might be open to helping others also in the future, and as a result, the culture of volunteering may spread even more in the examined area. Conclusion. Despite all the difficulties and social tensions caused by the war, Transcarpathian young people actively participated in voluntary work and successfully completed the tasks assigned to them.
Volunteer Activities of Students from Transcarpathia during the Russian-Ukrainian War of 2022
Keywords: студентство; волонтерство; російсько-українська війна у 2022 році; допомога біженцям / внутрішньо переміщеним особам; мотивації для волонтерів